Islamic Banking : Experiences in the Islamic Republic of Iran and Pakistan. (IMF Working Papers; Working Paper ;, 1989)
In an Islamic system, as interest is prohibited, banks are expected to operate solely on the basis of profit and risk sharing. This paper describes the developments in Islamic banking in Iran and Pakistan. As these two countries have initiated the most far-reaching experiments with Islamic banking, their experiences have a significant bearing on the feasibility of such a system. The developments in these countries are evaluated against the theory underlying the Islamic banking, and suggestions are made to achieve a more efficient system.